Toward Synthetic Intrinsically Disordered Polypeptides (IDPs): Controlled Incorporation of Glycine in the Ring-Opening Polymerization of N -Carboxyanhydrides - Badreldin, Mostafa; Salas-Ambrosio, Pedro; Bourasseau, Sylvain; Lecommandoux, Sebastien; Harrisson, Simon; Bonduelle, Colin (Biomacromolecules, 2024)
Intrinsically disordered proteins (IDPs) do not have a well-defined folded structure but instead behave as extended polymer chains in solution. Many IDPs are rich in glycine residues, which create steric barriers to secondary structuring and protein folding. Inspired by this feature, we have studied how the introduction of glycine residues influences the secondary structure of a model polypeptide, poly(l-glutamic acid), a helical polymer. For this purpose, we carried out ring-opening copolymerization with γ-benzyl-l-glutamate and glycine -carboxyanhydride (NCA) monomers. We aimed to control the glycine distribution within PBLG by adjusting the reactivity ratios of the two NCAs using different reaction conditions (temperature, solvent). The relationship between those conditions, the monomer distributions, and the secondary structure enabled the design of intrinsically disordered polypeptides when a highly gradient microstructure was achieved in DMSO.